Term limits and voter turnout - Veiga, Francisco José (2017)
This paper studies the impact of term limits on voter turnout, using the recent introduction of term limits at the local government level in Portugal as a natural experiment. Although instrumental, expressive, and information-based theories of voter participation imply eﬀects of term limits on turnout, this is clearly an under-researched topic. Applying a diﬀerence-in-diﬀerences approach to data at both the municipal and parish levels, we ﬁnd strong evidence that the introduction of term limits increased voter participation. Our results contrast with previous ﬁndings for California and demonstrate that more re search on this topic is clearly necessary.